Psychological emergency and mental health worker´s: systematic review - Laudelino Neto, Alessandra (2017)
The Psychological Emergency, a mode of clinical-psychological care of an emergency type, is configured as a flexible care practice, especially regarding temporal and relational dimensions, which has been changing and permeating different contexts in the contemporary world. Thus, the objective of this work was to investigate the scientific production on the Psychological Emergency and Mental Health of the Worker. Therefore, a systematic review study was carried out with concepts from the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) methodology, in the following electronic databases: LILACS and MEDLINE from the access by regional portal of the VHL, PePSIC, SCIELO, Portal of CAPES journals, and the Brazilian Digital Library of Theses and Dissertations (BDTD), covering the period from 2010 to 2016. The predominant profile found is composed of qualitative studies, based on the theoretical references of the Person Centered Approach ACP) and the Existential Phenomenology. It is important to note the existence of few studies involving the theme of the present review.